Forecasting approach of ultimate bearing capacity of underreamed anchor under local shear failure - Zheng, Bin; Bayat, Mahmoud; Shi, Yehui; Jiang, Yazhou; Qian, Xiangdong; Novák, Drahomír; Cao, Maosen (Elsevier, 2025)
The end resistance formula in the current industry specification has parameters that are difficult to determine precisely, resulting in estimated results often does not reflect the true condition of underreamed anchor. To address this problem, based on the elucidation of load transfer law when local shear damage occurs in the soil around anchor under vertical pulling action of underreamed anchor, a model of end resistance of underreamed anchor is proposed. The model can calculate the end resistance while avoiding uncertainty of parameters of current formula. Numerical simulations and field tests show that the proposed model significantly improves the accuracy of calculating end resistance of underreamed anchor.

The end resistance formula in the current industry specification has parameters that are difficult to determine precisely, resulting in estimated results often does not reflect the true condition of underreamed anchor. To address this problem, based on the elucidation of load transfer law when local shear damage occurs in the soil around anchor under vertical pulling action of underreamed anchor, a model of end resistance of underreamed anchor is proposed. The model can calculate the end resistance while avoiding uncertainty of parameters of current formula. Numerical simulations and field tests show that the proposed model significantly improves the accuracy of calculating end resistance of underreamed anchor.
Forecasting approach of ultimate bearing capacity of underreamed anchor under local shear failure
Keywords: Underreamed anchor; End resistance model; Local shear failure; Underreamed anchor; End resistance model; Local shear failure